If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(15x + 25) = 435 Reorder the terms: 3(25 + 15x) = 435 (25 * 3 + 15x * 3) = 435 (75 + 45x) = 435 Solving 75 + 45x = 435 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-75' to each side of the equation. 75 + -75 + 45x = 435 + -75 Combine like terms: 75 + -75 = 0 0 + 45x = 435 + -75 45x = 435 + -75 Combine like terms: 435 + -75 = 360 45x = 360 Divide each side by '45'. x = 8 Simplifying x = 8
| 4x-(x+2)=12+2(x+4) | | 8+12b-26+6b=0 | | f(-3)=x^2+1 | | 15x-10=225 | | (15+3x)-x=65 | | 3.9y+9.6=8.7y | | 4x-x+2=12+2(x+4) | | 2b+6=9b+11 | | 7(2x+4)=77 | | 12x-20=12x | | 4(-4-8x)+28x+4x=-273 | | 3(x^2+5x+6)=0 | | 4+b=1 | | -20=4(d-2) | | 1+j=2 | | -0.3+r=4 | | 4x-x+12=12+2(x+4) | | 19+j=107 | | 16=4(X-3) | | n-14=-20 | | 3p-9=90 | | (x-6-2i)(x-6+2i)=0 | | 120000(x-100)+150((X^2)-400+40000)=22536(600-x) | | 3p-9=180 | | -7(3+6p)+p=12-8p | | -2(d+5)=-4 | | 12y+6=2(6y+1) | | 2(443+88)=56 | | 28+-4x=-64 | | 12x=c+25 | | f(-3)=-2x+3 | | -5(X+3)+2x=45 |